Flake Electrical Conductivity of Few-Layer Graphene - Hamze Mousavi; Jabbar Khodadadi (The Scientific World Journal)
The Kubo formula for the electrical conductivity of per stratum of few-layer graphene, up to five, is analytically calculated in both simple and Bernal structures within the tight-binding Hamiltonian model and Green's function technique, compared with the single-layer one. The results show that, by increasing the layers of the graphene as well as the interlayer hopping of the nonhybridized pz orbitals, this conductivity decreases. Although the change in its magnitude varies less as the layer number increases to beyond two,distinguishably, at low temperatures, it exhibits a small deviation from linear behavior. Moreover, the simple bilayer graphene represents more conductivity with respect to the Bernal case.